Taylor & Francis Open Access Survey: Exploring Authors Views of Taylor & Francis and Routledge Authors Victoria Babbit - Babbit, Victoria (Septentrio Conference Series, 2014)
See video of the presentation. In late 2012 and the early part of 2013, Taylor & Francis conducted an author survey to investigate views on Open Access, peer review, re-use, metrics and licensing. The survey drew responses from over 14 700 authors and has provided insight into authors’ attitudes towards publishing, access and re-use in this changing publishing climate. Greater interest in licensing and re-use from authors, learned societies and editors derives, in part, from the establishment of institutional and funder OA publication mandates. While there appears to be growing support for the CC-BY license from certain sectors of the academic publishing community, the Taylor & Francis survey found that there is some concern about the wholesale application of CC-BY licenses and the types of re-use this license permits. This presentation will focus on the survey findings regarding re-use and licensing and explore some of the areas of concern voiced by our authors.